Анна Каренина: роман / Л. Н. Толстой - Толстой Лев Николаевич (Библиотека российской классики, 1994)
Экземпляры: ф. 3 (20140203) / Инвентарный номер: 100573 / Цена: 30.00 / Авт.знак: Т 53 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1